Developing Integrative-Prismatic Interdisciplinary Teaching Materials to Enhance Error Analysis Skills - Kholid, M. Ridho; Kholid, M. Fikri Nugraha (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to develop and evaluate integrative-prismatic-based interdisciplinary teaching materials for an error analysis course in the English department at a higher education institution. The research employed a three-phase method: (1) design and development of teaching materials, (2) implementation, and (3) data analysis. Participants included 60 English department students, selected through purposive sampling to ensure diverse representation in terms of gender, linguistic background, and academic proficiency. The instruments used were pre- and post-tests, classroom observations, semi-structured interviews, focus groups, and student artifacts such as assignments and reflective journals. Data were collected over a 10-week period, during which the teaching materials were integrated into the course curriculum. Quantitative data from pre- and post-tests were analyzed using paired sample t-tests to assess improvements in students' error analysis skills, while qualitative data from observations, interviews, and focus groups were analyzed thematically to identify changes in engagement, critical thinking, and interdisciplinary learning. The findings revealed significant improvements in students’ abilities to identify, categorize, and correct errors using interdisciplinary approaches, as well as increased engagement and development of critical thinking skills. These results suggest that the integrative-prismatic framework is effective in fostering deeper learning and adaptability among students. The study implies that such interdisciplinary materials can be valuable for curriculum development in higher education, but further research is needed to validate these findings across different courses and contexts to establish broader applicability and effectiveness.